2003
DOI: 10.1258/002367703103051895
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the sensitivity of in vivo antibody production tests with in vitro PCR-based methods to detect infectious contamination of biological materials

Abstract: Bacteria and viruses may be transmitted to laboratory rodents by contaminated biological materials such as transplantable tumours, cell lines, sera or other biological materials. Biological materials are currently being screened using the mouse or rat antibody production (MAP/RAP) test (serological testing). We decided to test and validate an alternative assay using polymerase chain reaction (PCR/realtime PCR) technology to detect viral contamination directly in biological material. The aim of this study there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…PCR assays appear to be most useful for the identification of parvoviruses in contaminated biomaterials (Bauer et al 2004;Blank et al 2004;Bootz et al 2003), target tissues from infected rodents (e.g., mesenteric lymph node and spleen) (Besselsen 1998;Besselsen et al 1995;Redig and Besselsen 2001;Wan et al 2006), and potentially infected feces and environmental surfaces Kunita et al 2006;Ueno et al 1997).…”
Section: Detectionmentioning
confidence: 99%
“…PCR assays appear to be most useful for the identification of parvoviruses in contaminated biomaterials (Bauer et al 2004;Blank et al 2004;Bootz et al 2003), target tissues from infected rodents (e.g., mesenteric lymph node and spleen) (Besselsen 1998;Besselsen et al 1995;Redig and Besselsen 2001;Wan et al 2006), and potentially infected feces and environmental surfaces Kunita et al 2006;Ueno et al 1997).…”
Section: Detectionmentioning
confidence: 99%
“…Total DNA from each diluted washing drop was extracted using the QIAamp DNA mini kit (Qiagen, Hilden, Germany) according to the manufacturer's instructions. The primers used were those designed by Bootz et al [42] as follows: 5 0 -GAGCGCCATCTAGTGAGC-3 0 (forward) and 5 0 -ATTTGCCTGTGCTGGCTG-3 0 (reverse), yielding a 483-bp product. A double-distilled water sample served as a negative PCR control.…”
Section: Virological Examination Of Washing Dropsmentioning
confidence: 99%
“…To this end, fertilized oocytes and morulae were exposed to different concentrations of MMVp for 16 h, while 2-cell embryos and blastocysts were coincubated for 1 h. In addition, morulae were exposed to MHV-A59 for 16 h. One group of embryos was washed, and the remaining embryos remained unwashed before embryo transfer. Serological analyses were performed by means of ELISA to detect antibodies to MHV or MMV in recipients and in progeny on Days 14,21,28,42, and 63 and on Days 42,63, 84, 112, 133, and 154, respectively, after embryo transfer. Coincubation with a minimum of 10 5 /ml of fluorescent microspheres showed that particles with a diameter of 20 nm but not 100 nm crossed the ZP of murine blastocysts.…”
mentioning
confidence: 99%
“…Total DNA from each diluted drop was extracted using the QIAamp DNA mini kit (Qiagen, Hilden, Germany) according to the manufacturer's instructions. The primers used were those designed by Bootz et al [27] as follows: 5 0 -GAGCGCCATCTAGT GAGC-3 0 (forward) and 5 0 -ATTTGCCTGTGCTGGCTG-3 0 (reverse), yielding a 483-base pair (bp) product. A double-distilled water sample served as a negative PCR control.…”
Section: Virological Examination Of Washing Drops and Embryosmentioning
confidence: 99%